The Effect of Factors Related to Mergers or Acquisitions on the Performance of the Acquirer Firms - Habib, Adnan (2011)
This paper investigates the direct effect of merger or acquisition (represented by horizontal, vertical, and conglomerate type of mergers; cross-border or local type of mergers; firm’s threshold; cash, share or undisclosed method of payment; total debt of the acquirer; financial leverage of acquirer; size of the acquirer; value of the deal; and time interval in between the announcement date and completion date of the merger) and also the indirect effect through corporate governance factors, like number of cross-board membership of CEO of the acquirer, and the number of board members of the acquirer on the corporate performance (represented by Tobin’s Q ratio and Return on Asset) of the acquirer of 30 global acquisitions that occurred during and after the recent economic crisis in between 2007 and 2009. There were six models that were tested based on the time period (before the acquisition, after the acquisition, and cumulative time) and the measure of performance (market based, and accounting based). Some of the models had majority of the factors insignificant which was assumed to be due to the small sample size. The factors that were mostly affected by the smaller sample size are firm threshold, CEO’s cross-board directorship, total debt, and time interval between announcement and completion date. The factors that had significant effect on firm performance based on the results of this paper are: conglomerate type of mergers, cross-border mergers, and methods of payment. Whereas vertical and horizontal type of mergers, financial leverage, size of the acquirer, and value of the deal did not show any significant relationship with the acquirer’s corporate performance based on the result of this paper.